The Impact of Lampenflora on Cave-dwelling Arthropods in Gunungsewu Karst, Java, Indonesia - Kurniawan, Isma Dwi; Rahmadi, Cahyo; Ardi, Tiara Esti; Nasrullah, Ridwan; Willyanto, Muhammad Iqbal; Setiabudi, Andy (Biosaintifika: Journal of Biology & Biology Education, 2018)
The development of wild caves into show caves is required an installation of electric lights along the cave passages for illumination and decoration purposes for tourist attraction. The presence of artificial lights can stimulate the growth of photosynthetic organisms such as lampenflora and alter the typical cave ecosystem. The study was aimed to detect the effect of lampenflora on cave-dwelling arthropods community. Four caves were sampled during the study, 2 caves are show caves with the existence of lampenflora and 2 others are wild caves without lampenflora. Arthropods sampling were conducted by hand collecting, pitfall trap, bait trap and berlese extractor. Lampenflora comprises of algae (Phycophyta), moss (Bryophyta) and fern (Pteridophyta) grow mostly around white light lamps. Richness, diversity, and evenness indices of Arthropods are higher in caves with the existence of lampenflora compared to caves without lampeflora. This study clearly shows that the presence of lampenflora can increase Arthropods diversity and suppress dominancy of common Arthropods species in caves, also increasing the relative abundance of predators. This condition will shift the ecosystem equilibrium and lead to cave ecosystem destruction. The results of this study should be a scientific consideration for show cave development and management. Lampenfloras have to be removed from all caves and preventive efforts should be taken to minimize their growth.